PERAN PENTING ARBITRASE DALAM HUKUM PERKAWINAN ISLAM DI INDONESIA (Urgensitas Lembaga Arbitrase Islam dalam Pengasuhan Anak dan Sengketa Perceraian) - Idrus, Muhammad (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2024)
The role of marital arbitration carried out by the Religious Courts and BP4 in Indonesia are considered of contextualization of marital arbitration which already existed in the early days of Islam. The advisory body for the development and preservation of marriage is an organization that is semi-official as a support for the duties of the ministry of religion in the field of marriage and aims to improve the quality of marriage, prosperous and eternal family according to Islamic teachings while marital disputes are household relations between husband and wife who are in dispute in marriage. This study discusses about the urgency of role of the Religious Courts and the advisory body for the development and preservation of marriage in mediating childcare cases and marital disputes. The role of BP4 in resolving marriage disputes is as a marriage consultant, by providing explanations, guidance to the parties to the dispute, namely the guardian, with the prospective bride through the institution of the Marriage Counseling, Development and Preservation Agency. The discussion of this study uses a descriptive method of analysis. Some literatur are classified, and then used as the basis for analyzing the above problems.